Analysis of respiratory complications occasioned by the coronavirus (COVID-19): a systematic review - Gouveia, Guilherme Pertinni de Morais; Cunha, Samira Veras; da Silva, Rosangela Lago (Journal of Health & Biological Sciences, 2021)
Aim: To describe and analyze the main disorders in the respiratory system, in individuals with confirmed cases of COVID - 19 reported in the scientific literature. Methods: Systematic literature review, based on the flowchart of the “Preferred Reporting Items for Systematic Reviews and Meta-Analyzes” (PRISMA), including primary quantitative experimental or quasi-experimental studies, freely accessible articles, available in Portuguese, English, Spanish and published from 2019 to 2020, using the PICOS strategy. 8,543 articles during March and April 2020, through the Lilacs, Scielo, Pubmed, MedLine, PeDro, Cochrane, Science direct and Google academic databases and of these, the Start tool (State-of-the-Art through Systematic Review) managed 94 studies. Results: Studies showed that most individuals had admission with signs and symptoms of fever, dry cough, difficulty breathing, expectoration, nausea, vomiting, diarrhea and rare myalgia. reaching from children to the elderly and had some previous comorbidities. Conclusion: This review identified the emphatic onset of the disease since symptoms and respiratory complications appear between 3 and 14 days.